Peningkatan Keterampilan Anggota Masyarakat Karang Taruna di Kelurahan Kebon Pala melalui Sosialisasi dan Workshop Desain Mural - Grace Putri Dianty; Sahala Simatupang; Lourenza; Amadea GL Baginda; Ulinata (JURNAL ComunitÃ Servizio : Jurnal Terkait Kegiatan Pengabdian kepada Masyarakat, terkhusus bidang Teknologi, Kewirausahaan dan Sosial Kemasyarakatan, 2024)
The Community Service Activity carried out by the UKI Faculty of Engineering Architecture Study Program is entitled Green Action 34 Improving the Skills of Karang Taruna Community Members in Kebon Pala Village Through Socialization and Mural Design Workshops. This activity is a continuation of the previous Community Service Activity which aims to increase the skills of members of the Karang Taruna community in Kebon Pala Village by providing material provision through socialization and workshops. The method involves inviting resource persons to provide material to the participants and then holding a workshop by directly practicing how to paint a mural by choosing a location at the Kebon Pala Village Head Office as a pilot project in this activity. This Community Service activity provides paint sponsor Aviand Brands which prepares all the tools and materials for Mural activities in this mural activity. Participants will be given funds to buy paint and brushes so they can carry out workshop activities so that the results are satisfactory. The results show that the mural design can be completed well and obtain satisfactory results